99.3k views
0 votes
3(-5y+2)= 21 how do i solve this problem algebraically?

User Omer Mazig
by
4.6k points

2 Answers

3 votes

Answer:

Y= -1

Explanation:

Step 1: Simplify both sides of the equation.

3(−5y+2)=21

(3)(−5y)+(3)(2)=21(Distribute)

−15y+6=21

Step 2: Subtract 6 from both sides.

−15y+6−6=21−6

−15y=15

Step 3: Divide both sides by -15.

−15y −15 = 15 −15

Y= -1

User Nijogeorgep
by
4.6k points
4 votes

Answer:

Explanation:

1)expand out the bracket

-15y+6=21

2) get the y to one side

6=21+15y

3) solve

15=15y

1=y

User Shinil
by
4.6k points